Leprosy: Relationship between early diagnosis, number of dermatological injuries and degree of disability at the time of diagnosis in the state of Sergipe between 2010 and 2020 (Research, Society and Development, 2022)
Leprosy is a relevant public health problem, being a disease that generates, in addition to stigma, great impacts on the individual's social life, as it is an infectious disease with the power to generate physical disabilities. Objective: To trace the epidemiological profile of leprosy cases in order to point out the number of leprosy lesions, the affected nerves and the early diagnosis of the disease. Methods: Cross-sectional, descriptive and quantitative study. Available information on leprosy was consulted in the Notifiable Diseases Information System (SINAN), for the period between 2010 and 2020. The study variables were divided into the number of notifications of the disease, related to: sex, age group, degree of sequelae , clinical presentation, degree of disability and number of skin lesions. Results: It was observed in the study that the frequency of reported cases remained constant over the years, with a higher prevalence of male and middle-aged patients. In addition, there was a predominance of the clinical form most susceptible to leprosy reactions, borderline leprosy, with a number of lesions greater than five. Regarding the degree of disability, it was observed that the prevalence is higher in patients with grade 0. Conclusion: The prevalence of leprosy is still high and early diagnosis and rapid initiation of treatment are essential to reduce the mortality rate and complications caused by the disease.